Efficacy and Tolerability of IncobotulinumtoxinA for Treating Glabellar Frown Lines in Korean Adults: A Postmarketing Observational Study. (December 2017) - Park, Je-Young; Sung, Nak-Kwan; Pitt, Jonathan M.
Abstract : BACKGROUND: IncobotulinumtoxinA is safe and effective in Caucasian adults. Its effects have been less documented in Asian adults. OBJECTIVE: To describe the efficacy and tolerability of incobotulinumtoxinA for treating glabellar frown lines (GFLs) in South Korean adults. METHODS: South Korean adults aged 18 to 65 years with moderate-to-severe GFLs received a single dose of 10 to 28 U incobotulinumtoxinA during routine clinical practice. After 30 ± 14 days, investigators assessed the efficacy using the Global Aesthetic Improvement Scale and rated tolerability using a 4-point scale. RESULTS: Six hundred seventy-three subjects were enrolled, of which 528 completed the study according to protocol. Glabellar frown lines improved in 98.7% (521/528) of subjects, with 30.8% of cases rated as "very much improved" and 47.4% as "much improved." The extent of improvement was unaffected by sex, age, and weight but was greater when the time between GFL identification and treatment was <6 months ( p < .001) and when concomitant aesthetic nondrug treatments were used ( p < .001). For 94% of subjects, tolerability was good or very good. All reported adverse events were transient and mild or moderate in severity. CONCLUSION: IncobotulinumtoxinA was well tolerated and effective for treating moderate-to-severe GFLs in Korean adults irrespective of age, sex, or weight.